1999
DOI: 10.1007/bf02752342
|View full text |Cite
|
Sign up to set email alerts
|

Microbial profile of neonatal infection in coimbatore

Abstract: In this study, 187 consecutive neonates suspected of having septicaemia were investigated for isolation of micro organisms. Two samples of blood were collected for isolation of aerobes and anaerobes. Cultures were positive in 75 (40%) cases. Aerobic bacteria were the major etiological agent, accounting for 93% of positives including the 8% cases showing polymicrobial etiology. Anaerobic bacteria and Candida species were isolated in 6.6% and 8% of positive cases respectively. Bacteroides fragilis (amongst anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
2
5
2
Order By: Relevance
“…aureus was the predominantly isolated pathogen in this study; similar findings were seen in several studies [9,10]. Group B Streptococcus, which is a common cause of neonatal sepsis in the west, is infrequent in India and in other tropical countries [11].…”
Section: Discussionsupporting
confidence: 88%
“…aureus was the predominantly isolated pathogen in this study; similar findings were seen in several studies [9,10]. Group B Streptococcus, which is a common cause of neonatal sepsis in the west, is infrequent in India and in other tropical countries [11].…”
Section: Discussionsupporting
confidence: 88%
“…Staphylococcus aureus was the most common organism in our study which was comparable to different studies. 5,11,12 Mortality in our study was 4 % which differed from different studies done in Pakistan, Bangladesh and Nigeria which showed mortalities of 30.9%,20.6% and 20.3% respectively. 13,14,15 This probably resulted from the fact that our neonatal care unit was of level II contrast to the centres of these studies which were level III .…”
Section: Discussioncontrasting
confidence: 97%
“…The report of the National Neonatal Perinatal database showed Klebsiella as the predominant (29%) pathogen. 19,20 The clinical significance of relatively low virulence isolates, such as CONS and Enterococcus is difficult to ascertain. These organisms can cause true bacteremia or their isolation may represent simple contamination.…”
Section: Discussionmentioning
confidence: 99%